2018
DOI: 10.1039/c8mt00225h
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometallated Au(iii) dithiocarbamate complexes: synthesis, anticancer evaluation and mechanistic studies

Abstract: A series of cationic mixed cyclometallated (C^N)Au(iii) dithiocarbamate complexes has been synthesized in good yields [HC^N = 2-(p-t-butylphenyl)pyridine]. The crystal structure of [(C^N)AuS2CNEt2]PF6 (3) has been determined. The cytotoxic properties of the new complexes have been evaluated in vitro against a panel of human cancer cell lines and healthy cells and compared with a neutral mixed (C^C)Au(iii) dithiocarbamate complex (C^C = 4,4'-di-t-butylbiphenyl-2,2'-diyl). The complexes appeared to be susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 72 publications
0
39
0
Order By: Relevance
“…6A and B). These complexes collectively are more cytotoxic towards the cell line MDA-MB-231 in comparison to the [C^N]Au(III)DTC complexes prepared by Bochmann et al 45 The different [C^N] backbone presented here proves to be a critical component in drug design and overall improvement of cytotoxic efficacy. The cytotoxicity of complexes 1a and 2a towards TNBC's is quite promising as these cell lines are typically cisplatin resistant.…”
Section: Anticancer Activity In Vitromentioning
confidence: 52%
See 3 more Smart Citations
“…6A and B). These complexes collectively are more cytotoxic towards the cell line MDA-MB-231 in comparison to the [C^N]Au(III)DTC complexes prepared by Bochmann et al 45 The different [C^N] backbone presented here proves to be a critical component in drug design and overall improvement of cytotoxic efficacy. The cytotoxicity of complexes 1a and 2a towards TNBC's is quite promising as these cell lines are typically cisplatin resistant.…”
Section: Anticancer Activity In Vitromentioning
confidence: 52%
“…S84-S103 †). Whereas gold dithiocarbamates are known to react with thiols, 45,49,51,69 detailed studies to unravel the potential mechanism of activity do not exist. HPLC trace of the reaction solution revealed one distinct band at a different retention time (R t -5.00 minutes) from 2a (R t -6.03 minutes) or GSH (R t -1.72 minutes) ( Fig.…”
Section: Reactivity Of Gold(iii) Dithiocarbamates With Cysteine Thiolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, researchers have investigated widely about metal-based complexes for cancer therapy, with various types of metallic antitumor candidates being developed for decades, such as gold (Au) and Au-NHCs complexes (Fung et al, 2017; Porchia et al, 2018; Williams et al, 2018), ruthenium (Ru) complexes (Tan et al, 2010), iridium (Ir) complexes (Cao et al, 2013), iron (Fe) complexes (Gou et al, 2016), etc. For instance, Che et al found that Au (III) complexes containing special ligand could act as smart fluorescent probes and anticancer agents (Zou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%